Digital radio over fiber transmission technique for millimeter-wave radio access network - Jia YE; Jianwei LUO; Yi GUO; Wei PAN (物联网学报, 2019)
As the air interface standard of 5G confirms the millimeter wave as one important frequency band for the signal carrier,millimeter-wave communication is considered as the key technique to improve the transmission performance of the mobile communication system.Firstly,the digital radio over fiber (DRoF) link in 5G application was introduced.Then,the different quantization coding algorithms applied in DRoF system were compared and summarized.In order to provide reference for the construction of millimeter-wave radio access network,the important performance indexes such as the error vector amplitude (EVM),system complexity and spectrum utilization were analyzed.